Piezoelectric films using hybrid technology for ultrasonic array and electronic device applications - Chao, Chen (2008)
Lead zirconate titanate (PZT) films are promising for MEMS type micro-devices applications because of their high electromechanical coupling coefficients and excellent piezoelectric properties. PZT piezoelectric film integrated on silicon substrate for various MEMS devices has been the subject of considerable attention in recent years. In this thesis, a broad range of work is presented, including the deposition of PZT films onto silicon substrates, the development of a novel interferometric system and related method for piezoelectric characterization of PZT films, as well as the design and fabrication of diaphragm-type piezoelectric micromachined ultrasonic transducer arrays.